2003
DOI: 10.1098/rstb.2002.1222
|View full text |Cite
|
Sign up to set email alerts
|

How long will long-term potentiation last?

Abstract: The paramount feature of long-term potentiation (LTP) as a memory mechanism is its characteristic persistence over time. Although the basic phenomenology of LTP persistence was established 30 years ago, new insights have emerged recently about the extent of LTP persistence and its regulation by activity and experience. Thus, it is now evident that LTP, at least in the dentate gyrus, can either be decremental, lasting from hours to weeks, or stable, lasting months or longer. Although mechanisms engaged during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
180
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(187 citation statements)
references
References 93 publications
3
180
0
4
Order By: Relevance
“…It was reported that exercise could promote long-term potentiation (LTP) (Van Praag et al, 1999). This is significant as it is widely accepted that LTP may serve as a model for some of the molecular and synaptic events underlying memory (Abraham, 2003), including the formation of dendritic spine (Toni et al, 1999). It is also interesting to note that such increased LTP might be the result of increased endogenous neurotrophic factors due to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that exercise could promote long-term potentiation (LTP) (Van Praag et al, 1999). This is significant as it is widely accepted that LTP may serve as a model for some of the molecular and synaptic events underlying memory (Abraham, 2003), including the formation of dendritic spine (Toni et al, 1999). It is also interesting to note that such increased LTP might be the result of increased endogenous neurotrophic factors due to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, repeated, strong high frequency stimulations (e.g. multiple trains of 100 pulses at 100 Hz) can induce an increase in synaptic efficacy lasting over 8 hours (Frey, Krug, Reymann, and Matthies, 1988) or even days (Abraham, 2003). L-LTP differs from E-LTP in its requirement for de novo mRNA and in its association with structural changes at synapses (Frey et al, 1988;Harris, Fiala, and Ostroff, 2003;Kandel, 2001;Krug, Lossner, and Ott, 1984;Muller, Nikonenko, Jourdain, and Alberi, 2002;Yuste and Bonhoeffer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The LTP, at least its superficial manifestation of enhanced postsynaptic response to presynaptic stimulation, is only temporary; the synaptic changes seldom last more than a few weeks (Abraham, 2003). The next few subsections make a case that the superficially detectable synaptic change fits into a much wider process whereby a permanent memory trace is installed.…”
Section: A New Cell Assembly Announces Itself By Inducing Ltpmentioning
confidence: 99%